Silicon-carbon composite material and method of making, negative electrode, and energy storage device

CN122950460APending Publication Date: 2026-10-20LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611424901.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有材料缺乏这样一套以“极低闭孔、高密度、高压实”为核心、且可由常规物理手段定量表征并便于品控的参数体系

Benefits of technology

[0017]本发明具有以下有益效果:本发明提供一种氮气不可进入体积小于0.05cm3/g、骨架密度为1.9g/cm3~2.2g/cm3的硅碳复合负极材料,通过极低闭孔率与高骨架密度的协同,使复合颗粒趋于致密,在有限体积内最大化活性硅负载与体积能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a silicon-carbon composite material and its preparation method, a negative electrode electrode, and an energy storage device, relating to the field of lithium-ion battery technology. This invention provides a nitrogen-free volume of less than 0.05 cm³. 3 / g, skeletal density is 1.9g / cm³ 3 ~2.2g / cm 3 The silicon-carbon composite anode material achieves high density by combining extremely low closed-pore ratio with high framework density, resulting in compact composite particles that maximize active silicon loading and volumetric energy density within a limited volume. Furthermore, the invention utilizes a graphitized carbon framework, nano-silicon grains, and appropriate amounts of metal elements (aluminum, nickel, manganese) to maintain electron / ion conduction, alleviate lithium intercalation stress, and improve the interface, thus achieving a balance between high volumetric energy density and long-cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to silicon-carbon composite materials and their preparation methods, negative electrode electrodes, and energy storage devices. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and environmental friendliness, have become the core energy storage device for new energy vehicles, consumer electronics, and large-scale energy storage. As the demand for longer driving ranges continues to increase, the capacity bottleneck of traditional graphite anodes (theoretical specific capacity of only 372 mAh / g) is becoming increasingly apparent. Replacing graphite with silicon-based materials to construct high-capacity anodes has become an industry consensus. Elemental silicon boasts advantages such as an ultra-high theoretical specific capacity of 3579 mAh / g, a low lithium intercalation potential, and abundant reserves. However, its volume expansion during lithium intercalation, reaching approximately 300%, easily leads to problems such as active particle pulverization, electrode cracking, and rapid capacity decay.

[0003] Combining silicon with porous carbon is a mainstream technological approach to mitigate expansion. Among these, silicon-carbon composites, prepared by chemical vapor deposition of silicon onto a porous carbon framework, have attracted significant attention due to their ability to buffer expansion through pores and the continuous conductive network provided by the carbon framework. In the industrialization of silicon-carbon anodes, industry focus on pore structures has largely centered on low-density approaches that use closed-pore structures to buffer expansion, i.e., constructing numerous nitrogen-inaccessible closed-pore cavities to accommodate silicon expansion. However, over-reliance on closed pores sacrifices the material's volumetric energy density, primarily because while closed pores provide buffering, they do not contribute to capacity themselves and increase the inactive space per unit volume.

[0004] In contrast, another technical approach involves minimizing the proportion of closed pores and increasing the skeleton density and electrode compaction density while maintaining appropriate pore size to balance ion transport and limited expansion capacity. This results in denser composite particles, maximizing the active silicon load within a limited volume and significantly improving the cell's volumetric energy density. The key to this approach lies in controlling the nitrogen-inaccessible volume to an extremely low level (less than 0.05 cm³). 3 While maintaining a high skeleton density (1.9~2.2 g / cm³), it also exhibits high skeletal density. 3 The high compaction density, combined with the graphitized carbon framework, avoids uncontrolled expansion and conductivity degradation caused by densification. Furthermore, nanoscale silicon grains (average diameter less than 50 nm) and appropriate amounts of metal elements (aluminum, nickel, manganese) improve the lithium intercalation stress distribution and interfacial conductivity. Existing materials lack a parameter system centered on "extremely low closed-pore, high density, and high compaction," which can be quantitatively characterized by conventional physical methods and is easy to control in terms of quality. Therefore, there is an urgent need in this field for a nitrogen-free volume of less than 0.05 cm³. 3 / g of high-density porous silicon-carbon composite material to achieve a balance between high volumetric energy density and long-cycle stability within a limited volume.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide silicon-carbon composite materials and their preparation methods, negative electrode electrodes, and energy storage devices, with the aim of significantly improving volumetric energy density.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a silicon-carbon composite material, comprising a porous carbon framework and silicon at least partially filled within the porous carbon framework, wherein the silicon mass fraction in the silicon-carbon composite material is 20% to 85%, and the framework density is 1.9 g / cm³. 3 ~2.2g / cm 3 Nitrogen gas must not enter a volume smaller than 0.05 cm³. 3 / g.

[0008] In an optional implementation, the nitrogen-free volume is 0.01 cm³. 3 / g~0.04cm 3 / g; And / or, the skeleton density is 2.0 g / cm³. 3 ~2.2g / cm 3 ; And / or, silicon is introduced and prepared by chemical vapor deposition (CVD) at a deposition temperature of 380°C to 800°C.

[0009] In an optional embodiment, the porous carbon framework has a graphitized structure that satisfies at least one of the following features (a) to (c): Feature (a): The intensity ratio of the D band to the G band in the Raman spectrum of the porous carbon framework I D / I G The value is 0.5 to 0.95. Feature (b): The size of the graphite crystallites La, calculated by Raman spectroscopy, of the porous carbon framework is 2 nm to 100 nm. Feature (c): The X-ray diffraction crystallinity of the porous carbon framework is 10% to 80%.

[0010] In an optional embodiment, the porous carbon framework has a total pore volume of 0.5 cm³, as determined by nitrogen adsorption. 3 / g~2.5cm 3 / g, and the proportion of micropore volume in its pore size distribution is >10%, preferably >80%; And / or, the ratio of pore volume to silicon volume in the silicon-carbon composite material is (0.3~1.0):1; And / or, the average particle size of the silicon-carbon composite material is 3~15μm, preferably 5~10μm; And / or, it also contains a metallic element selected from at least one of aluminum, nickel and manganese, and the total content of the metallic element is <50,000 ppm; And / or, the particles of the silicon-carbon composite material contain silicon grains with an average diameter of less than 50 nm.

[0011] In an optional embodiment, the silicon-carbon composite material comprises a carbonaceous surface layer that at least partially covers its surface; Preferably, the carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material; Preferably, the carbonaceous surface layer is formed by carbonization of a carbon-containing polymer.

[0012] Secondly, the present invention provides a method for preparing any of the silicon-carbon composite materials described in the foregoing embodiments, comprising: A porous carbon framework precursor is provided: a carbon source is porousened and then mixed with a graphitization catalyst for graphitization heat treatment to obtain a porous carbon framework with a graphitized structure; wherein the framework density of the porous carbon framework is 1.9 g / cm³. 3 ~2.2g / cm 3 Nitrogen gas must not enter a volume smaller than 0.05 cm³. 3 / g; Silicon deposition: Silicon is deposited using fluidized bed chemical vapor deposition. The deposition rate is controlled to allow the silicon phase to fill the porous carbon framework as nanocrystals with an average diameter of less than 50 nm, ultimately achieving a silicon mass fraction of 20%–85% and a nitrogen-inaccessible volume of less than 0.05 cm³. 3 / g; Construction of carbonaceous surface layer: Silicon-deposited particles are mixed with carbon-containing polymers and carbonized to form a carbonaceous surface layer that at least partially covers the particle surface and is at least partially graphitized. The proportion of the carbonaceous surface layer is controlled to be 1% to 20% of the total mass. Grading and characterization: The average particle size was controlled to be 3~15μm by sieving, and the parameters were characterized.

[0013] In an optional embodiment, the carbon source is selected from at least one of pitch-based, resin-based, biomass-based, and metal-organic framework-derived carbon; The graphitization catalyst is a compound containing a metal element, wherein the metal element is selected from at least one of K, Co, Ni, Cr, Fe, Mn, Al, Cu and Zn; Preferably, the graphitization temperature of the high-temperature graphitization heat treatment is 700℃~1600℃, and the treatment time is 2h~24h; Preferably, the silicon deposition step includes: placing a porous carbon framework in a fluidized bed reactor, introducing a mixed gas containing a silicon precursor and an inert carrier gas or hydrogen, and performing deposition at a deposition temperature of 350°C to 800°C; controlling the volume fraction of the silicon precursor in the mixed gas to be 1% to 80%, and the system pressure to be 1 kPa to 100 kPa. More preferably, the silicon-containing precursor is selected from at least one of silane, dichlorosilane, trichlorosilane and silicon tetrachloride.

[0014] In an alternative embodiment, at least one of aluminum, nickel, and manganese is introduced before or after silicon deposition via vapor-phase doping or solution impregnation-reduction.

[0015] Thirdly, the present invention provides a negative electrode comprising a silicon-carbon composite material according to any one of the foregoing embodiments or a silicon-carbon composite material prepared by any one of the foregoing embodiments.

[0016] Fourthly, the present invention provides an energy storage device comprising the silicon-carbon composite material of any of the foregoing embodiments or the negative electrode of the foregoing embodiments; Preferably, the energy storage device is a lithium-ion secondary battery.

[0017] The present invention has the following beneficial effects: The present invention provides a nitrogen-free volume of less than 0.05 cm³. 3 / g, skeletal density is 1.9g / cm³ 3 ~2.2g / cm 3 The silicon-carbon composite anode material achieves a high degree of density by combining extremely low closed-pore ratio with high framework density, thus maximizing the active silicon loading and volumetric energy density within a limited volume.

[0018] In a preferred embodiment, a graphitized carbon framework, nano-silicon grains, and appropriate amounts of metal elements (aluminum, nickel, manganese) are used to maintain electron / ion conduction, alleviate lithium intercalation stress, and improve the interface, thereby achieving a balance between high volumetric energy density and long-term cycle stability. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 A schematic diagram of the microstructure of the silicon-carbon composite material provided in an embodiment of the present invention; Figure 2This diagram illustrates the relationship between the volume of nitrogen-free space and the skeleton density (helium gravity method) and compaction density. Figure 3 This is a process flow diagram for preparing silicon-carbon composite materials according to an embodiment of the present invention.

[0021] Icons: 001 - Carbonaceous surface; 002 - Porous carbon framework; 003 - Nano-silicon grains; 004 - Closed pores. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0023] To overcome the limitations of existing silicon-carbon composite anode materials, which rely excessively on closed-cell buffering and thus have limited volumetric energy density, as well as the technical defects that easily occur during high densification, such as uncontrolled expansion, conductivity and interface degradation, this invention provides a silicon-carbon composite anode material with very few closed cells, high skeleton density and high compaction density, which maximizes the active silicon load within a limited volume and significantly improves the volumetric energy density of the cell compared to conventional silicon-carbon materials.

[0024] This invention also provides a silicon-carbon composite material, such as... Figure 1 As shown, the porous carbon framework 002 is filled with nano-silicon grains 003, and a carbonaceous surface layer 001 is also disposed on the porous carbon framework 002. The porous carbon framework 002 has closed pores 004. The silicon-carbon composite material provided in this embodiment of the invention has extremely low closed pores, high density and high compaction, and with the synergy of nano-silicon grains and metal, it achieves a balance between high volumetric energy density and long-term cycling stability. Figure 1 This exhibits a structure in which silicon is filled within a dense porous carbon framework, with extremely low closed pores, a carbonaceous surface layer, and nano-silicon grains.

[0025] The parameters are explained one by one below. All tests for the core performance parameters were conducted using industry-standard equipment and methods: [Silicon mass fraction] The mass fraction of silicon in silicon-carbon composite materials is 20% to 85%, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., or any value between the above adjacent values.

[0026] Specifically, the silicon mass fraction refers to the proportion of silicon in the total mass of the composite material, calculated as: silicon mass / total mass of composite material × 100%. Testing methods include: air-atmospheric thermogravimetric analysis (TGA oxidation method) (carbon burnout, silicon oxidation to SiO2 conversion), or ICP-OES / EDS elemental quantitative analysis for verification.

[0027] The silicon mass percentage, calculated based on the total mass of the composite material, directly determines the upper limit of the anode specific capacity and is a core indicator for achieving high energy density. In this invention, the silicon mass fraction is limited to 20%~85% (preferably 25%~85%), maximizing specific capacity under a highly dense structure. If the silicon content is too low, the capacity is insufficient; if the silicon content is too high, the silicon phase proportion is too large, the total expansion increases, and the dense framework cannot support the load. When the silicon mass fraction is below 20%, the proportion of active material is insufficient, resulting in a significant decrease in specific capacity and volumetric energy density, thus losing the advantage of high capacity.

[0028] Nitrogen gas must not enter the volume. The nitrogen-free volume of the silicon-carbon composite material provided in this embodiment of the invention is less than 0.05 cm³. 3 / g, such as 0.01cm 3 / g, 0.015cm 3 / g, 0.02cm 3 / g, 0.025cm 3 / g, 0.03cm 3 / g, 0.035cm 3 / g, 0.04cm 3 / g, etc., can also be any value between the above adjacent values, preferably 0.01cm. 3 / g~0.04cm 3 / g.

[0029] Specifically, the nitrogen-inaccessible volume refers to the pore volume (mainly including closed pores and some ultramicropores) that nitrogen molecules cannot enter under nitrogen adsorption conditions at 77K, measured in cm. 3 / g. The determination and calculation formula is as follows: V N2 =1 / ρ sk 1 / ρ0 V open ; V N2 This represents the closed-pore volume in which nitrogen cannot enter; V open The total accessible (opening) pore volume (cm³) measured by nitrogen adsorption method (refer to GB / T 19587 and GB / T 21650). 3 / g); ρ sk The skeleton density (g / cm³) measured by the helium gas specific gravity method. 3), ρ0 is the theoretical density calculated according to the mixing rule based on the phase composition of the composite material (ρ0=1 / (w Si / ρ Si +w C / ρ C ), ρ Si =2.33g / cm 3 ρ C =2.20g / cm 3 w Si w is the mass fraction of silicon. C The mass fraction of carbon can be simply calculated as w. C= 1-w Si ).

[0030] The nitrogen-inaccessible volume (closed-cell volume) reflects the total amount of pores within the composite material that are isolated from each other and not connected to the outside. The nitrogen-inaccessible volume of the silicon-carbon composite material provided in this invention is extremely low (less than 0.05 cm³). 3 / g), which means that the pores are mainly open pores with very few closed pores, making the material dense, which is a prerequisite for increasing the volumetric energy density. The upper limit is set to less than 0.05cm³. 3 / g (preferably 0.01~0.04cm) 3 / g), which can maximize the compression of inactive closed-cell space, increase the active silicon load and electrode compaction within a limited volume, thereby significantly improving the cell volumetric energy density, while maintaining appropriate opening to maintain ion transport.

[0031] It should be noted that when nitrogen gas cannot enter, the volume must be at least 0.05 cm³. 3 At / g, the number of closed pores increases, the material becomes more porous, the volumetric energy density decreases, and the advantages of conductivity and expansion brought about by densification are weakened.

[0032] [Skeleton density] The skeletal density of the composite particles (determined by helium gravity) is 1.9 g / cm³. 3 ~2.2g / cm 3 For example, it can be 1.9g / cm 3 2.0g / cm 3 2.05g / cm 3 2.1g / cm 3 2.15g / cm 3 2.2g / cm 3 etc., or any value between the above adjacent values, preferably 2.0 g / cm 3 ~2.2g / cm 3 .

[0033] The true density of the framework, measured by helium density determination, is intrinsically linked to the closed-cell volume. Higher framework density indicates fewer closed cells per unit mass and a denser material, forming the structural basis for high volumetric energy density. In this embodiment of the invention, the framework density is limited to 1.9 g / cm³. 3 ~2.2g / cm 3 (Preferred 2.0g / cm) 3 ~2.2g / cm 3 ), and less than 0.05cm 3 Extremely low nitrogen levels ( / g) prevent the entry of nitrogen into the volumetric synergy, ensuring the composite material is highly dense without losing volumetric energy density due to excessive porosity. If the skeleton density is too low, it will lead to a resurgence of closed-cell structures and loss of density; when the skeleton density is less than 1.9 g / cm³... 3 At that time, the material has insufficient density and more closed pores, resulting in a decrease in volumetric energy density and electrode compaction capacity.

[0034] Specifically, the skeleton density ρ sk This refers to the skeletal (true) density of the composite particles, measured in g / cm³. 3 The helium specific gravity method (refer to GB / T 40401-2021) (helium specific gravity meter) was used, based on the gas displacement method. The dynamic diameter of helium atoms is about 0.26 nm, which can enter pores except for a very small number of ultramicropores. The volume of the skeleton was obtained by mass / volume after measurement.

[0035] A schematic diagram showing the relationship between the volume of nitrogen that cannot enter and the skeleton density (helium specific gravity method) and compaction density is shown below. Figure 2 As shown.

[0036] [Graphitized structure] The porous carbon framework possesses a graphitized structure; the degree of graphitization of the carbon framework is determined by Raman spectroscopy. D / I G Characterization is achieved by at least one of the following: graphite crystallite size (La) and X-ray diffraction crystallinity, reflecting the electronic conductivity and mechanical strength of the carbon skeleton.

[0037] The intensity ratio of the D band to the G band in the Raman spectrum of porous carbon frameworks is I D / I GThe value is 0.5–0.95, and can be 0.5, 0.6, 0.7, 0.75, 0.8, 0.9, 0.95, or any value between these adjacent ranges. The graphite crystallite size La, calculated by Raman spectroscopy, of the porous carbon framework is 2 nm–100 nm, and can be 2 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, or any value between these adjacent ranges. The X-ray diffraction crystallinity of the porous carbon framework is 10%–80%, and can be 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60%, 70%, 80%, or any value between these adjacent ranges.

[0038] It should be noted that the graphitized structure is limited to at least one of the above characteristics, allowing the carbon framework to maintain continuous conductivity and adequate mechanical support even at high density; excessive amorphous structure results in poor conductivity, while excessive graphitization makes it difficult to form the necessary openings. When graphitization is severely insufficient (such as I...), D / I G When the carbon skeleton is greater than 0.95 (approaching amorphous carbon), its electrical conductivity is poor, electron conduction is hindered, and rate and cycle performance decreases.

[0039] Specifically, the Raman spectrum is taken from the D band (approximately 1350 cm⁻¹). -1 ) and G-band (approximately 1580cm) -1 The integral intensity ratio; La is calculated empirically from the Raman half-width; XRD is obtained from the ratio of the integral intensity of the (002) peak to the total diffraction intensity.

[0040] [Pore volume and pore size distribution] The porous carbon framework has a total pore volume of 0.5 cm³, as determined by nitrogen adsorption. 3 / g~2.5cm 3 / g, such as 0.5cm 3 / g, 0.8cm 3 / g, 1.1cm 3 / g, 1.4cm 3 / g, 1.7cm 3 / g, 2.0cm 3 / g, 2.5cm 3 / g, etc., can also be any value between the above adjacent values. The pore volume ratio of micropores in its pore size distribution is >10%, such as 11%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 85%, 90%, 95%, 98%, etc., preferably >80%.

[0041] It should be noted that the total accessible pore volume and the proportion of micropores / mesopores / macropores, determined by nitrogen adsorption, describe the development and size composition of the open pore network. In this invention, the total pore volume is 0.5 cm³. 3 / g~2.5cm 3 / g can retain necessary ion transport channels and limited expansion capacity under dense conditions. The total pore volume in this embodiment of the invention is limited to 0.5 cm³. 3 / g~2.5cm 3 / g, with a micropore content >10%, preferably >80%. This distribution results in moderate open pores and extremely low closed pores, balancing ion transport and volumetric energy density. When the micropore content is less than 10% (e.g., up to 15%), excessive microporosity increases the tendency to close pores, disrupts the dense main structure, leads to an imbalance between expansion and transport, and deteriorates cycle performance.

[0042] Specifically, the total pore volume / pore size distribution refers to the total volume of pores into which nitrogen can enter and the proportion of micro / meso / macro pores, according to IUPAC: micropores <2 nm, mesopores 2~50 nm, macropores >50 nm. Testing method: Nitrogen adsorption at 77 K; total pore volume and the proportion of each pore size segment are calculated using the BET specific surface area and BJH / DFT model; 20 Å~100 Å is equivalent to 2~10 nm, and 200 Å is equivalent to 20 nm.

[0043] [Pore volume to silicon volume ratio] The ratio of pore volume to silicon volume in silicon-carbon composite materials is (0.3~1.0):1, such as 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, etc.

[0044] Specifically, the pore volume / silicon volume ratio refers to the ratio of the pore volume that the framework can enter to the silicon volume, and the ratio of the framework nitrogen-enterable pore volume to the silicon phase volume. The testing method involves converting the total nitrogen adsorption pore volume to the silicon mass fraction (silicon density 2.33 g / cm³). 3 Find the ratio.

[0045] It should be noted that the ratio of the volume of accessible pores to the volume of the silicon phase reflects the degree of matching between the pores and the silicon deposition. In dense pathways, this ratio is lower, indicating that the pore space is efficiently filled with silicon. In this embodiment of the invention, this ratio is limited to 0.3:1 to 1:1, ensuring that the accessible pore space just adequately accommodates the deposited silicon, avoiding density decrease due to excess pores or uncontrolled expansion due to excessive silicon. If the ratio is too high (too many pores), there will be insufficient active silicon per unit mass, resulting in a decrease in volumetric energy density. When the ratio of pore volume to silicon volume is greater than 1:1, there is an excess of silicon relative to the pores, insufficient active silicon loading, and a significant decrease in specific capacity and volumetric energy density.

[0046] [Particle size] The average particle size of the silicon-carbon composite material is 3~15μm, preferably 5~10μm. The particles of the silicon-carbon composite material contain silicon grains with an average diameter of less than 50nm, and the average diameter can be statistically observed by dark-field / high-resolution transmission electron microscopy (TEM).

[0047] The average grain size of the silicon phase was determined using transmission electron microscopy. Nanoscale silicon grains can shorten the lithium-ion diffusion path, disperse lithium intercalation stress, and alleviate expansion concentration caused by high silicon loading and dense structure. In this embodiment of the invention, the average diameter of the silicon grains is limited to less than 50 nm, so that the silicon phase exists in nanocrystalline form, which, together with the open pores and graphitized framework, achieves stress dispersion. If the grain size is too large, the stress concentration within the grains increases, and the risk of lithium intercalation cracking increases. When the average diameter of the silicon grains is not less than 50 nm (such as reaching 80 nm), the lithium intercalation stress within the grains concentrates, leading to increased expansion and cyclic degradation.

[0048] Specifically, the average particle size of silicon-carbon composite material refers to the median particle size of the composite material, which is the particle size corresponding to 50% of the cumulative volume. It is measured by a laser particle size analyzer (dry or wet dispersion) and is denoted as Dv50.

[0049] Silicon is introduced and prepared by chemical vapor deposition. The deposition temperature of chemical vapor deposition is 380℃~800℃, such as 380℃, 430℃, 480℃, 530℃, 580℃, 630℃, 800℃, etc., or any value between the above adjacent values.

[0050] [Carbonous surface] The silicon-carbon composite material comprises a carbonaceous surface layer that at least partially covers its surface; the carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material, such as 1%, 4%, 7%, 10%, 13%, 16%, 20%, etc., or any value between these adjacent values. The carbonaceous surface layer is formed by carbonization of a carbon-containing polymer and is at least partially graphitized.

[0051] It should be noted that the carbonaceous surface layer, which at least partially covers the surface of the composite material, serves to isolate the active material from the electrolyte and improve interfacial stability and conductivity; at least partial graphitization can further reduce interfacial impedance. In this embodiment of the invention, the proportion of the carbonaceous surface layer is limited to 1% to 20% of the total mass of the composite material, and preferably derived from the carbonization of a carbon-containing polymer and possessing at least a partially graphitized structure. This can improve the interface and first-cycle efficiency and reduce impedance without excessively increasing the inactive mass. When the proportion of the carbonaceous surface layer is greater than 20%, the excessive inactive carbon mass dilutes the active silicon, reduces the specific capacity, and decreases the first-cycle coulombic efficiency due to additional surface side reactions.

[0052] Specifically, the carbonaceous surface layer is obtained by a coating-carbonization process, and its proportion is determined by subtracting the total mass difference or by thermogravimetric analysis.

[0053] [Metallic elements] The silicon-carbon composite material provided in this embodiment of the invention also contains metallic elements, which are selected from at least one of aluminum, nickel, and manganese. The metallic elements can be any one or more of these elements, and these metallic elements are components that can improve conductivity and interface properties. The total content of metallic elements is <50,000 ppm.

[0054] It should be noted that the metallic elements (aluminum, nickel, or manganese) included in the composite material can improve interfacial conductivity, promote lithium-ion migration kinetics, and stabilize the interfacial film, thereby improving rate performance and cycle life. Limiting the metallic elements to aluminum, nickel, or manganese is advantageous because these three metals have good compatibility with silicon-carbon systems, are low in cost, and do not introduce significant side reactions; appropriate doping can compensate for conductivity and interfacial shortcomings in a highly dense structure. Introducing other metals not belonging to aluminum, nickel, or manganese (such as iron, which easily catalyzes electrolyte decomposition or forms undesirable interfacial phases) can trigger side reactions and worsen first-efficiency and cycle life.

[0055] Specifically, the metallic element is introduced through an alloying / mixing process, and qualitatively and quantitatively determined by EDS or ICP-OES, and is limited to aluminum, nickel or manganese.

[0056] In summary, the silicon-carbon composite material provided by the embodiments of the present invention maximizes the active silicon loading within a limited volume to improve the volumetric energy density through the synergy of extremely low closed-pore ratio, high framework density, and high compaction density. Furthermore, it maintains electron / ion conduction, alleviates lithium intercalation stress, and improves the interface by using graphitized carbon framework, nano-silicon grains (average diameter less than 50 nm), and appropriate amounts of metal elements (aluminum, nickel, manganese), thereby achieving a balance between high volumetric energy density and long-term cycling stability.

[0057] This invention also provides a method for preparing silicon-carbon composite materials, the process flow diagram of which is shown below. Figure 3 The steps are as follows: S1. Preparation of porous carbon framework precursor A porous carbon framework with a graphitized structure is prepared by activating and pore-forming a carbon source, followed by graphitization heat treatment with a mixed carbon source and graphitization catalyst. The graphitized structure satisfies condition I. D / I G The nanoparticle size is 0.5~0.95 nm, the La content is 2~100 nm, and the XRD crystallinity is 10%~80%; the skeletal density of the porous carbon framework is 1.9 g / cm³. 3 ~2.2g / cm 3 (Helium gravity method) Nitrogen gas must not enter a volume smaller than 0.05 cm³. 3 / g is a dense porous carbon skeleton with very few closed pores.

[0058] In some embodiments, the carbon source is selected from at least one of pitch-based, resin-based, biomass-based, and metal-organic framework-derived carbon, and the carbon source can be any one or more of the above. Specifically, it can be phenolic resin, coconut shell, bamboo, coal, pitch, etc. The graphitization catalyst is a compound containing a metal element, and the metal element is selected from at least one of K, Co, Ni, Cr, Fe, Mn, Al, Cu, and Zn, and the metal element can be any one or more of the above.

[0059] Furthermore, the graphitization temperature of the high-temperature graphitization heat treatment is 700℃~1600℃ (e.g., 700℃, 800℃, 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃, etc.), and the treatment time is 2h~24h (e.g., 2h, 5h, 8h, 10h, 13h, 15h, 18h, 20h, 24h, etc.). By controlling the graphitization temperature and the degree of pore formation, the volume of nitrogen gas that cannot enter is less than 0.05cm. 3 / g.

[0060] S2, Vapor-deposited silicon Silicon was deposited using fluidized bed chemical vapor deposition, allowing the silicon phase to fill the porous carbon framework with nanocrystals of average diameter less than 50 nm, ultimately achieving a silicon mass fraction of 20%–85% and a nitrogen-inaccessible volume of less than 0.05 cm³. 3 / g.

[0061] In practice, the silicon deposition process includes: placing a porous carbon framework in a fluidized bed reactor, introducing a mixture of silicon-containing precursor and inert carrier gas or hydrogen, and depositing at a deposition temperature of 350℃ to 800℃. The volume fraction of the silicon-containing precursor in the mixed gas is controlled to be 1% to 80%, and the system pressure is 1 kPa to 100 kPa. By controlling the silane volume fraction, system pressure, and deposition time, the silicon phase is filled into the porous carbon framework as nanocrystals with an average diameter of less than 50 nm, ultimately achieving a silicon mass fraction of 20% to 80% and a nitrogen-inaccessible volume of less than 0.05 cm³. 3 / g.

[0062] Specifically, the deposition temperature can be 350℃, 380℃, 400℃, 430℃, 450℃, 480℃, 500℃, 530℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, etc. The volume fraction of the silicon-containing precursor can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc. The system pressure can be 1 kPa, 10 kPa, 20 kPa, 40 kPa, 60 kPa, 80 kPa, 100 kPa, etc.

[0063] In some embodiments, the silicon-containing precursor is selected from at least one of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride, and the silicon-containing precursor can be any one or more of the above.

[0064] S3, doped with metallic elements Before and after silicon deposition, at least one metal element from aluminum, nickel, and manganese is introduced through vapor phase doping or solution impregnation-reduction. The introduced metal element can be any one or more of the above. Introducing specific types of metal elements can improve conductivity and interface.

[0065] Both vapor-phase doping and solution impregnation-reduction methods are existing processes, and the specific process steps and parameters are not limited.

[0066] S4, Surface carbon coating Silicon-deposited particles are mixed with a carbon-containing polymer and carbonized to form a carbonaceous surface layer that at least partially covers the particle surface and is at least partially graphitized. The proportion of the carbonaceous surface layer is controlled to be 1% to 20% of the total mass.

[0067] In some embodiments, the carbon-containing polymer may be asphalt, phenolic resin, polyvinyl alcohol, etc.

[0068] S5. Grading and Characterization The average particle size was controlled to be 3~15μm by sieving, and the framework density, nitrogen-inaccessible volume, pore size distribution and silicon grain size were confirmed to fall within the specified range by helium gravity method, nitrogen adsorption method, transmission electron microscopy and in-situ transmission electron microscopy.

[0069] This invention also provides a negative electrode comprising the silicon-carbon composite material provided in this invention, and using the silicon-carbon composite material as the negative electrode active material to prepare the negative electrode.

[0070] This invention also provides an energy storage device, comprising the silicon-carbon composite material provided in this invention or the negative electrode provided in this invention. The specific form of the energy storage device is not limited, such as a lithium-ion secondary battery.

[0071] Specifically, the silicon-carbon composite material or the negative electrode provided in the embodiments of the present invention is suitable for lithium-ion battery scenarios that pursue high volumetric energy density and long cycle life, such as high volumetric energy density power batteries for new energy vehicles, consumer electronics, and large-scale energy storage.

[0072] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0073] The present invention is further illustrated below through specific embodiments and comparative examples. All embodiments fall within the requirements of the present invention regarding parameters such as silicon mass fraction, compaction density, framework density, and nitrogen-free volume. The comparative examples illustrate the necessity of limiting parameters by demonstrating the deviation of a single parameter from the specified limits.

[0074] All samples were tested under the same conditions, as follows: framework density was determined by helium gravity; total pore volume, pore size distribution, and accessible pore volume were determined by nitrogen adsorption at 77 K, and measured according to V... N2 =1 / ρ sk 1 / ρ0 V open Calculate the volume inaccessible to nitrogen; determine the silicon mass fraction using air TGA; characterize the graphitized structure using Raman / XRD; statistically analyze the average diameter of silicon grains using transmission electron microscopy; confirm the metal elements using EDS / ICP-OES; measure the first-cycle coulombic efficiency and 0.1C reversible specific capacity of a half-button cell; characterize the cycle life by measuring the capacity retention rate after 500 cycles of 4C charge / 1C discharge; improve the volumetric energy density of the cell by comparing it with a conventional silicon-carbon benchmark cell of equivalent design.

[0075] Example 1 The preparation steps of the silicon-carbon composite material provided in this embodiment are as follows: Step (1), Preparation of asphalt-based porous carbon: The asphalt raw material is pre-oxidized at 250℃ in an O2 atmosphere, then heated to 600℃ and held for 6 hours in an inert atmosphere, and then heated to 900℃ and held for 2 hours for carbonization to obtain asphalt-based carbon material; The asphalt-based carbon material is mixed with graphitization catalyst NiCl3 at a mass ratio of 100:0.5 and activated at 950℃ for 1.5 hours in an inert atmosphere (nitrogen) to obtain an activated product; The activated product is then subjected to acid washing, water washing and drying to obtain the asphalt-based porous carbon with graphitized structure I. D / I G =0.70, La=25nm, XRD crystallinity 35%, total pore volume of nitrogen adsorption 1.05cm³ 3 / g (85% micropores, 15% mesopores); Step (2): The porous carbon is placed in a fluidized bed and heated to 550°C in an argon atmosphere; then SiH4 gas (volume fraction 50%) carried by argon is switched and deposited for 6 hours under a system pressure of 5 kPa; SiH4 is stopped and the mixture is cooled to room temperature in argon to obtain silicon-carbon material.

[0076] Step (3): The above product is heated to 500°C under an inert atmosphere (nitrogen), and then a mixture of carbon source gas (acetylene) and carrier gas is introduced. The volume fraction of carbon source gas is 10%. The mixture is deposited at a constant temperature for 2 hours to allow the carbon source to decompose and deposit on the particle surface to form a carbon coating layer. After the deposition is completed, the mixture is cooled to room temperature under an inert atmosphere to obtain the carbon-coated silicon-carbon composite material. The carbon source gas flow rate is 200 sccm, and the carrier gas is nitrogen with a flow rate of 500 sccm.

[0077] The resulting product has a silicon mass fraction of 55%, an average particle size of 7.5 μm, an average silicon grain diameter of 2 nm, a carbonaceous surface layer content of 2%, and a framework density of 2.1 g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.01 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.03cm³. 3 / g.

[0078] Example 2 The preparation method in this embodiment is the same as that in Example 1, except that a resin-based dense porous carbon framework and a graphitized structure I are used. D / I G =0.65, La=22nm, XRD crystallinity 32%, total pore volume 0.78cm³ 3 / g (micropores 89%, mesopores 11%); fluidized bed CVD deposition of silicon (silane volume fraction 50%, system pressure 12kPa, deposition at 490℃ for 7.0 h), yielding silicon with a mass fraction of 53%, an average particle size of 8.1μm, an average silicon grain diameter of 2.2nm, a carbonaceous surface layer content of 1.5%, and a framework density of 2.08g / cm³. 3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.01 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.029cm³. 3 / g.

[0079] Example 3 The preparation method in this embodiment is the same as that in Example 1, except that a metal-organic framework is used to derive a dense porous carbon skeleton, and a graphitized structure I is formed. D / I G =0.75, La=28nm, XRD crystallinity 38%, total pore volume 0.55cm³ 3 / g (71% micropores, 29% mesopores); fluidized bed CVD deposition of silicon (50% silane volume fraction, system pressure 18 kPa, deposition at 470℃ for 4.5 h), with 1.5% aluminum introduced; yielding silicon with a mass fraction of 35%, an average particle size of 8.5 μm, an average silicon grain diameter of 2.5 nm, a carbonaceous surface layer content of 1.3%, and a framework density of 2.05 g / cm³.3 The silicon-carbon composite material, and the pore volume of the silicon-carbon composite particles measured by nitrogen gas is 0.005 cm³. 3 / g, calculations show that nitrogen cannot enter a volume of 0.043cm³. 3 / g.

[0080] Comparative Example A Using the same asphalt raw material as in Example 1, the porous carbon preparation process was adjusted (to form closed pores inside the porous carbon) to maintain the same deposited silica content of 55%, while reducing the skeleton density to 1.80 g / cm³. 3 This prevents nitrogen from entering, increasing the volume to 0.109 cm³. 3 / g (too large), the rest is the same as in Example 1.

[0081] The difference between the preparation process of the porous carbon provided in this comparative example and that in Example 1 is as follows: For the preparation of pitch-based porous carbon: Pitch raw material is pre-oxidized at 250°C in an O2 atmosphere, and then carbonized directly at 500°C for 2 hours under an inert atmosphere to obtain pitch-based carbon material. The pitch-based carbon material is mixed with graphitization catalyst NiCl3 at a mass ratio of 100:0.5 and activated at 950°C for 1.5 hours under an inert atmosphere to obtain an activated product. The activated product is then subjected to acid washing, water washing, and drying to obtain the pitch-based porous carbon.

[0082] Comparative Example B Using the same asphalt raw material as in Example 1, the silica mass fraction was reduced to 45% by decreasing silica deposition, resulting in a skeleton density of 1.90 g / cm³. 3 Nitrogen gas cannot enter, and the corresponding volume increases to 0.08 cm³. 3 / g.

[0083] The method for reducing the skeleton density provided in this comparative example differs from that in Example 1 in that: in step (2), porous carbon is placed in a fluidized bed and heated to 580°C under an argon atmosphere; then, SiH4 gas (80% by volume) carried by argon is switched, and deposition is carried out for 4.5 hours under a system pressure of 5 kPa; the SiH4 is then stopped, and the material is cooled to room temperature in argon to obtain silicon-carbon material. This process adjustment results in the deposition of silicon on the surface, with closed pores forming inside the internal particles, thereby reducing the skeleton density.

[0084] Comparative Example C Using the same asphalt raw material as in Example 1, the preparation process of porous carbon was adjusted (forming closed pores inside the porous carbon); in addition, by reducing silicon deposition, the silicon mass fraction was reduced to 40%, and the skeleton density was reduced to 1.75 g / cm³. 3 This only prevents nitrogen from entering, increasing the volume to 0.114 cm³. 3 / g (too large), the rest is the same as in Example 1.

[0085] The method for reducing skeleton density provided in this comparative example differs from that in Example 1 in that: In step (1), the asphalt raw material is pre-oxidized at 250°C in an O2 atmosphere, and then carbonized by directly heating to 500°C and holding at that temperature for 2 hours in an inert atmosphere to obtain asphalt-based carbon material. The asphalt-based carbon material is then activated with graphitization catalyst NiCl3 at a mass ratio of 100:0.5 at 950°C for 1.5 hours in an inert atmosphere to obtain an activated product. The activated product is then subjected to acid washing, water washing, and drying to obtain the asphalt-based porous carbon.

[0086] In step (2), porous carbon is placed in a fluidized bed and heated to 580°C under an argon atmosphere; then, SiH4 gas (80% by volume) carried by argon is switched, and deposition is carried out for 3.5 hours at a system pressure of 10 kPa; the SiH4 is then stopped, and the mixture is cooled to room temperature in argon to obtain silicon-carbon material. This process adjustment results in the deposition of silicon on the surface, with closed pores forming inside the particles, thereby reducing the skeletal density.

[0087] Table 1 provides parameters for silicon-carbon composite materials in the examples and comparative examples.

[0088] Table 2 provides the parameters and properties of silicon-carbon composite materials in the examples and comparative examples.

[0089] This invention utilizes nitrogen-free gas in volumes smaller than 0.05 cm³. 3 The core constraint of / g reduces the closed-cell state of the composite material to an extremely low level, making the pores predominantly open-cell, in conjunction with a concentration of 1.9~2.2 g / cm³. 3 The high skeleton density and high compaction density maximize the active silicon load within a limited volume, fundamentally improving the cell's volumetric energy density. Meanwhile, the graphitized carbon skeleton (I... D / I G A continuous conductive and mechanical support is provided by a silicon nanoparticle (0.5–0.95 nm, La 5–100 nm, XRD crystallinity 10%–50%); nano-silicon grains with an average diameter of less than 50 nm disperse and accommodate lithium intercalation stress; appropriate amounts of aluminum, nickel, or manganese metal elements improve interfacial conductivity and migration kinetics; and a carbonaceous surface layer with at least partial graphitization further stabilizes the interface. Each parameter (nitrogen-inaccessible volume, framework density, compaction / particle density, silicon mass fraction, pore size distribution, porosity-to-silicon ratio, silicon grains, carbonaceous surface layer, metal elements, and average particle size) progressively defines and collectively constructs a structural system that unifies high volumetric energy density, excellent rate capability, and long-cycle stability.

[0090] In summary, the embodiments of the present invention provide a silicon-carbon composite material and its preparation method, a negative electrode electrode, and an energy storage device. Compared with the prior art, the present invention has the following significant advantages: (1) Significantly improved volumetric energy density: the volume inaccessible to nitrogen is less than 0.05 cm³. 3 / g means that there are very few closed pores and the pores are mainly open pores, combined with a high skeleton density (1.9~2.2g / cm³). 3 With high density, the active silicon load is maximized within a limited volume, and the cell volumetric energy density is increased by 15%~20% compared with conventional silicon-carbon materials.

[0091] (2) Controlled expansion and stable cycling: Despite the tendency to be dense, the present invention still uses an appropriate amount of open network, nano-silicon grains (<50nm) and graphitized carbon skeleton to synergistically accommodate and disperse lithium intercalation stress, so that the full charge volume expansion is controlled at a low level (better than 30% in the example), and the capacity retention rate of 4C charge / 1C discharge for 500 cycles can reach more than 90%.

[0092] (3) Excellent conductivity and interface: The graphitized carbon skeleton provides continuous electron conduction; the aluminum, nickel or manganese metal elements contained in the composite particles can improve the interfacial conductivity and lithium ion migration kinetics; the at least partially graphitized carbon surface further enhances the interfacial stability and first-cycle coulombic efficiency.

[0093] (4) Strong process adaptability: The low closed-pore, high-density structure can be prepared by fluidized bed chemical vapor deposition combined with high temperature graphitization and controllable carbonization process. The parameter system can be non-destructively characterized by conventional methods such as helium specific gravity method, nitrogen adsorption method, and transmission electron microscopy, which is convenient for industry to reproduce and control quality.

[0094] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that, The silicon-carbon composite material comprises a porous carbon framework and silicon at least partially filling the interior of the porous carbon framework, wherein the mass fraction of silicon in the silicon-carbon composite material is 20% to 85%, and the framework density is 1.9 g / cm³. 3 ~2.2g / cm 3 Nitrogen gas must not enter a volume smaller than 0.05 cm³. 3 / g.

2. The silicon-carbon composite material according to claim 1, characterized in that, Nitrogen gas cannot enter a volume of 0.01 cm³. 3 / g~0.04cm 3 / g; And / or, the skeleton density is 2.0 g / cm³. 3 ~2.2g / cm 3 ; And / or, the silicon is introduced and prepared by a chemical vapor deposition process, wherein the deposition temperature of the chemical vapor deposition is 380℃~800℃.

3. The silicon-carbon composite material according to claim 1, characterized in that, The porous carbon framework has a graphitized structure, which satisfies at least one of the following characteristics (a) to (c): Feature (a): The intensity ratio of the D band to the G band in the Raman spectrum of the porous carbon framework is I D / I G The value is 0.5 to 0.

95. Feature (b): The porous carbon framework has a graphite crystallite size La of 2 nm to 100 nm calculated according to Raman spectroscopy; Feature (c): The X-ray diffraction crystallinity of the porous carbon framework is 10% to 80%.

4. The silicon-carbon composite material according to claim 1, characterized in that, The porous carbon framework has a total pore volume of 0.5 cm³, as determined by nitrogen adsorption. 3 / g~2.5cm 3 / g, and the proportion of micropore volume in its pore size distribution is >10%; And / or, the ratio of pore volume to silicon volume of the silicon-carbon composite material is (0.3~1.0):1; And / or, the average particle size of the silicon-carbon composite material is 3~15μm; And / or, it also contains a metallic element selected from at least one of aluminum, nickel and manganese, and the total content of the metallic element is <50,000 ppm; And / or, the particles of the silicon-carbon composite material contain silicon grains with an average diameter of less than 50 nm.

5. The silicon-carbon composite material according to any one of claims 1 to 4, characterized in that, The silicon-carbon composite material comprises a carbonaceous surface layer that at least partially covers its surface; The carbonaceous surface layer accounts for 1% to 20% of the total mass of the silicon-carbon composite material; The carbonaceous surface layer is formed by carbonization of a carbon-containing polymer.

6. A method for preparing the silicon-carbon composite material according to any one of claims 1 to 5, characterized in that, include: A porous carbon framework precursor is provided: a carbon source is porousened and then mixed with a graphitization catalyst for graphitization heat treatment to obtain a porous carbon framework with a graphitized structure; wherein the framework density of the porous carbon framework is 1.9 g / cm³. 3 ~2.2g / cm 3 Nitrogen gas must not enter a volume smaller than 0.05 cm³. 3 / g; Silicon deposition: Silicon is deposited using fluidized bed chemical vapor deposition. The deposition rate is controlled to ensure that the silicon phase, consisting of nanocrystals with an average diameter of less than 50 nm, fills the porous carbon framework, ultimately achieving a silicon mass fraction of 20%–85% and a nitrogen-inaccessible volume of less than 0.05 cm³. 3 / g; Construction of a carbonaceous surface layer: Silicon-deposited particles are mixed with a carbon-containing polymer and carbonized to form a carbonaceous surface layer that at least partially covers the particle surface and is at least partially graphitized. The proportion of the carbonaceous surface layer is controlled to be 1% to 20% of the total mass. Grading and characterization: The average particle size was controlled to be 3~15μm by sieving, and the parameters were characterized.

7. The preparation method according to claim 6, characterized in that, The carbon source is selected from at least one of pitch-based, resin-based, biomass-based, and metal-organic framework-derived carbon; The graphitization catalyst is a compound containing a metal element, wherein the metal element is selected from at least one of K, Co, Ni, Cr, Fe, Mn, Al, Cu and Zn; The graphitization temperature for high-temperature graphitization heat treatment is 700℃~1600℃, and the treatment time is 2h~24h. The silicon deposition process includes: placing the porous carbon framework in a fluidized bed reactor, introducing a mixed gas of silicon-containing precursor and inert carrier gas or hydrogen, and performing deposition at a deposition temperature of 350°C to 800°C; controlling the volume fraction of the silicon-containing precursor in the mixed gas to be 1% to 80%, and the system pressure to be 1 kPa to 100 kPa. The silicon-containing precursor is selected from at least one of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride.

8. The preparation method according to claim 6, characterized in that, Before and after silicon deposition, at least one metallic element from aluminum, nickel, and manganese is introduced through vapor-phase doping or solution impregnation-reduction.

9. A negative electrode, characterized in that, The silicon-carbon composite material comprising any one of claims 1 to 5 or the silicon-carbon composite material prepared by any one of claims 6 to 8.

10. An energy storage device, characterized in that, The material comprises the silicon-carbon composite material according to any one of claims 1 to 5 or the negative electrode according to claim 9; The energy storage device is a lithium-ion secondary battery.